Mountain Rivers Reveal the Earthquake Hazard of Geologic Faults in Silicon Valley. Issue 19 (10th October 2022) - Aron, Felipe; Johnstone, Samuel A.; Mavrommatis, Andreas; Sare, Robert; Maerten, Frantz; Loveless, John P.; Baden, Curtis W.; Hilley, George E.
Abstract: The 1989, M w  = 6.9 Loma Prieta earthquake resulted in tens of lives lost and cost California almost 3% of its gross domestic product. Despite widespread damage, the earthquake did not clearly rupture the surface, challenging the identification and characterization of these hidden hazards. Here, we show that they can be illuminated by inverting fluvial topography for slip‐and moment accrual‐rates—fundamental components in earthquake hazard assessments—along relief‐generating geologic faults. We applied this technique to thrust faults bounding the mountains along the western side of Silicon Valley in the San Francisco Bay Area, and discovered that these structures may be capable of generating a M w  = 6.9 earthquake every 250–300 years based on moment accrual rates. This method may be deployed broadly to evaluate seismic hazard in developing regions with limited geological and geophysical information. Plain Language Summary: Large, shallow earthquakes nucleated along geologic faults promoting vertical motion of rocks produce instantaneous uplift of the Earth's surface on the order of meters. This process and the intervening deformations, repeated over thousands of earthquake cycles, build up mountain ranges, which are subsequently carved by rivers thanks to the action of climate forces counteracting tectonic uplift. Consequently, the incision pattern along mountain rivers, resulting from rock resistance to erosion and long‐lived distribution of fault‐induced rock uplift, contains information about the past activity of underlying relief‐generating faults. Our study tested this fundamental idea, integrating the topography with simple, yet standard mechanical and erosional modeling, to estimate the accrual of earthquake magnitude potential over time. We applied this new methodology, particularly useful to illuminate hazards posed by difficult‐to‐characterize‐faults not well exposed to direct observation, to the fault‐bounded mountains along the western side of the San Francisco Bay Area. We discovered that a quake of similar size to the 1989 Loma Prieta event, the last devastating earthquake affecting this populous economic hub, could occur every 250–300 years. More importantly, given the wide availability of topographic datasets, this method may be deployed broadly to evaluate seismic hazards in poorly instrumented and studied areas. Key Points: The topographic structure of mountain rivers can be inverted for long‐term slip‐and moment accrual‐rates along relief‐generating faults Thrust faults along the western side of Silicon Valley have the potential for generating a M w  = 6.9 earthquake every 250–300 years This approach may be deployed more broadly to evaluate seismic hazard in regions with limited geological and geophysical information